(untitled) (Oshada, 2025)
Emotional regulation is an important aspect in maintaining the mental health of the elderly, especially those suffering from chronic diseases such as Type 2 Diabetes Mellitus. Chronic disease conditions often trigger psychological stress that impacts an individual’s ability to manage emotions. One of the non-pharmacological interventions widely developed to overcome stress is Mindfulness-Based Stress Reduction (MBSR). This study aims to determine the effect of MBSR on emotional regulation in elderly with Type 2 Diabetes Mellitus in Bangun Rejo Village in 2025. This study used a quantitative design with a one-group pretest–posttest method. The study subjects were 30 elderly with Type 2 Diabetes Mellitus selected using a total sampling technique. The MBSR intervention was given for eight sessions, and emotional regulation was measured using the Emotion Regulation Questionnaire (ERQ) before and after the intervention. Data analysis was performed using descriptive statistics and the Paired Sample t-Test. The results showed a significant increase in emotional regulation scores, from an average of 34.67 before the intervention to 75.50 after the MBSR intervention. Statistical test results showed a significant difference between pretest and posttest scores (p < 0.05). Thus, MBSR has been proven effective in improving emotional regulation in elderly people with Type 2 Diabetes Mellitus. The MBSR program is recommended as a supporting intervention in elderly health services.